Degradable intelligent packaging material and preparation method thereof
Through the three-layer composite structure of degradable intelligent packaging materials, the problems of poor biodegradability and low functionality of traditional plastic packaging materials are solved, and efficient degradation, safety and versatility are achieved. It is suitable for food packaging and monitors storage temperature changes.
Patent Information
- Application Number
- CN202510665406.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-22
- Publication Date
- 2025-08-01
AI Technical Summary
Traditional plastic packaging materials have problems such as poor biodegradability, possible release of harmful substances, and low functionality, which affect food safety and environmental health.
It adopts a three-layer composite structure with a degradable intelligent packaging material. The inner layer contains chitosan, polylactic acid, tea polyphenols and temperature-sensitive color-changing powder. The intermediate layer contains microcellulose, ligno fibers and polyurethane elastomers. The outer layer contains anti-ultraviolet agents and degradable pigments. It is prepared by hot pressing composite and coating methods to achieve antibacterial, anti-ultraviolet, anti-pollution and degradable functions.
It has achieved efficient biodegradation, good safety and diversified functions, can monitor storage temperature changes, reduce the risk of food damage, and significantly improve environmental protection and safety.
Smart Images

Figure CN120396480A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of packaging materials, and in particular to a degradable intelligent packaging material and a preparation method thereof. Background Art
[0002] Food packaging can effectively prevent food from being contaminated by external pollutants and microorganisms, and can greatly extend the shelf life of food without affecting its quality. However, with the development of society, new requirements have been put forward for the multifunctionality of food packaging. Although plastic packaging is widely used in various food packaging, its potential threats to the environment and food safety have attracted increasing attention. Traditional plastic packaging materials, especially those mainly based on petroleum-based materials such as polyethylene (PE), polypropylene (PP), and polyvinyl chloride (PVC), although widely used in the market due to their low cost, good physical properties (such as water resistance, chemical resistance), etc., have also exposed a series of disadvantages:
[0003] (1) Traditional plastic packaging materials may release harmful substances during long-term use, especially under high-temperature conditions, and some harmful substances such as plasticizers, heavy metals, and monomers may migrate into food, affecting food safety;
[0004] (2) Traditional plastic packaging materials have poor biodegradability, seriously polluting the soil and water sources and threatening the health of the ecosystem;
[0005] (3) The functionality of traditional plastic packaging materials is relatively low and cannot meet the growing demand. Therefore, the present invention proposes a degradable intelligent packaging material and a preparation method thereof to solve the problems existing in the prior art. Summary of the Invention
[0006] Aiming at the above problems, the purpose of the present invention is to provide a degradable intelligent packaging material and a preparation method thereof. By combining multifunctional integration, biodegradability, environmental protection, and an efficient production process, the degradable intelligent packaging material and the preparation method can solve the problems existing in the prior art.
[0007] To achieve the object of the present invention, the present invention is realized through the following technical solutions: A degradable intelligent packaging material, the packaging material is a three-layer composite structure, namely an outer layer, an intermediate layer and an inner layer. The inner layer comprises the following raw materials in parts by weight: 40-50 parts of chitosan, 30-40 parts of first polylactic acid, 1-3 parts of tea polyphenols, 0.5-2 parts of thermochromic powder, 10-20 parts of pectin, and 0.5-2 parts of xylanase; the intermediate layer comprises the following raw materials in parts by weight: 10-20 parts of microcellulose, 5-10 parts of wood fiber, 1-5 parts of carbon fiber, 30-35 parts of second polylactic acid, 10-30 parts of first aqueous solution, 10-12 parts of sodium alginate, and 10-15 parts of polyurethane elastomer; the outer layer comprises the following raw materials in parts by weight: 1-5 parts of degradable pigment, 3-5 parts of ultraviolet absorber, 2-5 parts of bentonite, 1-3 parts of polytetrafluoroethylene, 10-30 parts of second aqueous solution, 0.5-1 part of dispersant, 0.5-1 part of surfactant, and 0.5-2 parts of coupling agent.
[0008] A further improvement lies in that: the thickness ratio of the outer layer, the intermediate layer and the inner layer is (3-4):(2-3):(3-4).
[0009] A further improvement lies in that: the particle size of the degradable pigment is ≤10μm; the particle size of the ultraviolet absorber is ≤150nm; the particle size of the bentonite is ≤10μm.
[0010] A further improvement lies in that: the dispersant is polyacrylate; the surfactant is polyvinyl alcohol; the thickener is carboxymethyl cellulose; the ultraviolet absorber is titanium dioxide; the coupling agent is silane coupling agent.
[0011] A preparation method of a degradable intelligent packaging material comprises the following steps:
[0012] Step 1. Treatment of the inner layer material
[0013] First, chitosan is stirred and dissolved by a solvent, then tea polyphenols, thermochromic powder and pectin are added, stirring is continued, and finally xylanase is added. After stirring for 15-30 min, a first mixed solution is obtained, and then it is added into a twin-screw extruder together with polylactic acid and extruded into a film to obtain the inner layer material;
[0014] Step 2. Treatment of the intermediate layer material
[0015] Microcellulose, wood fiber, carbon fiber, sodium alginate and the first aqueous solution are added into a high-shear stirring device for mixing to obtain a second mixed solution, and then it is added into a twin-screw extruder together with polylactic acid and polyurethane elastomer and extruded into a film to obtain the intermediate layer material;
[0016] Step 3. Treatment of the outer layer material
[0017] Add the degradable pigment, ultraviolet light protector, bentonite, polytetrafluoroethylene and the second aqueous solution into a high-shear stirring device, and add a dispersant, a thickener and a surfactant, then stir and mix them to obtain the outer layer material;
[0018] Step Four: Treatment of the composite structure
[0019] Use the hot pressing and composite method to composite the middle layer material and the inner layer material to obtain a double-layer composite structure. Then, use the coating method to coat the outer layer material onto the double-layer composite structure, and then perform hot pressing and composite again to obtain a three-layer composite structure, thus completing the preparation of the degradable intelligent packaging material.
[0020] A further improvement lies in that: in the said Step One, the solvent is an acetic acid solution, and the addition ratio of it to chitosan is 3 - 5:1.
[0021] A further improvement lies in that: in the said Step One, use the ultrasonic dispersion method for stirring, and the stirring time each time > 50 min.
[0022] A further improvement lies in that: in the said Step Two and Step One, the temperature in the twin-screw extruder is 170°C - 220°C.
[0023] The beneficial effects of the present invention are as follows:
[0024] (1) The present invention adopts a three-layer composite structure to achieve the functions of antibacterial, anti-ultraviolet, anti-pollution and degradable, forming a comprehensive protection. Compared with traditional packaging materials that usually can only provide a single function, the present invention has a wider application range, better environmental protection and better safety, and can avoid polluting the soil and water sources.
[0025] (2) In the inner layer material of the present invention, a temperature-sensitive color-changing powder is introduced, so that the packaging material has an intelligent response function, can change color following the change of temperature, helps users monitor the storage conditions of products, and reduces the risk of food damage due to improper storage temperature. Description of the Drawings
[0026] Figure 1 It is a schematic flow chart of the method of the embodiment of the present invention. Specific Embodiments
[0027] In order to deepen the understanding of the present invention, the following will further elaborate on the present invention in combination with embodiments. These embodiments are only used to explain the present invention and do not constitute a limitation to the protection scope of the present invention.
[0028] The thermochromic powder used in the embodiments of the present invention, also known as heat-sensitive color-changing powder, thermosensitive color-changing powder or temperature-indicating color-changing powder, is a special pigment that can change color according to temperature changes. Its color-changing mechanism is based on electron-transfer organic compounds, which have unique chemical structures. Under specific temperature conditions, the transfer of electrons causes changes in the molecular structure, thereby leading to color changes. This color-changing substance not only has bright colors but also can achieve reversible color changes from "colored to colorless" and "colorless to colored", which is incomparable to other reversible thermochromic substances such as heavy metal double salt complex type and liquid crystal type. The color-changing temperature thresholds of the thermochromic powder include -5°C, 0°C, 5°C, 10°C, 16°C, 21°C, 31°C, 33°C, 38°C, 43°C, 45°C, 50°C, 65°C, 70°C, 78°C, etc. In addition, the thermochromic powder can repeatedly change color as the temperature rises or falls.
[0029] Unless otherwise specified, the raw materials used in the embodiments of the present invention are all obtained through conventional commercial purchase channels.
[0030] Example 1
[0031] This example presents a degradable intelligent packaging material. The packaging material has a three-layer composite structure, namely an outer layer, an intermediate layer, and an inner layer. The inner layer includes the following raw materials in parts by weight: 40 parts of chitosan, 30 parts of the first polylactic acid, 1 part of tea polyphenols, 0.5 part of thermochromic powder, 10 parts of pectin, and 0.5 part of xylanase; the intermediate layer includes the following raw materials in parts by weight: 10 parts of microcrystalline cellulose, 5 parts of wood fiber, 1 part of carbon fiber, 30 parts of the second polylactic acid, 10 parts of the first aqueous solution, 10 parts of sodium alginate, and 10 parts of polyurethane elastomer; the outer layer includes the following raw materials in parts by weight: 1 part of degradable pigment, 3 parts of ultraviolet light absorber, 2 parts of bentonite, 1 part of polytetrafluoroethylene, 10 parts of the second aqueous solution, 0.5 part of dispersant, 0.5 part of surfactant, and 0.5 part of coupling agent. The dispersant is polyacrylate, the surfactant is polyvinyl alcohol, the thickening agent is carboxymethyl cellulose, the ultraviolet light absorber is titanium dioxide, and the coupling agent is silane coupling agent.
[0032] The thickness ratio of the outer layer, intermediate layer, and inner layer is 3:4:3.
[0033] The particle size of the degradable pigment is ≤10μm, the particle size of the ultraviolet light absorber is ≤150nm, and the particle size of the bentonite is ≤10μm.
[0034] According to Figure 1 As shown, this example provides a preparation method of a degradable intelligent packaging material, including the following steps:
[0035] Step 1. Treatment of the inner layer material
[0036] First, chitosan is added to a solvent (acetic acid solution) in a ratio of (1:5) and stirred for dissolution. During this process, the temperature is maintained at 55 °C. Then, tea polyphenols, thermochromic powder, and pectin are added, and stirring continues. During the above process, ultrasonic dispersion is used for stirring, and each stirring time is > 50 min. Finally, xylanase is added. At this time, the temperature is reduced to 25 °C. After stirring for 15 min, a first mixed solution is obtained. Then, it and polylactic acid are added to a twin-screw extruder at a temperature of 170 °C. After extrusion, a film is formed using a blown film machine to obtain the inner layer material.
[0037] Step Two: Treatment of the middle layer material
[0038] Microcrystalline cellulose, wood fiber, carbon fiber, sodium alginate, and a first aqueous solution are added to a high-shear stirring device for mixing. The mixing time is > 30 min to obtain a second mixed solution. Then, it, polylactic acid, and polyurethane elastomer are added to a twin-screw extruder for melt blending at a temperature of 170 °C. After extrusion, a film is formed using a blown film machine to obtain the middle layer material. During this process, the high-shear stirring device ensures that all materials are evenly dispersed in the solution, avoiding aggregation and stratification phenomena. This is crucial for improving the mechanical properties and stability of the middle layer material. The twin-screw extruder can provide efficient mixing and sufficient heat transfer during the blending process, ensuring the uniformity of each component and being able to control the extrusion temperature to prevent component degradation or performance loss due to excessive temperature.
[0039] Correspondingly, by adding reinforcing materials such as microcrystalline cellulose, wood fiber, and carbon fiber, the mechanical properties of the middle layer can be significantly improved, enhancing the tensile strength, tear resistance, and compressive resistance.
[0040] Furthermore, a dispersant can also be added during the mixing process.
[0041] Step Three: Treatment of the outer layer material
[0042] Add the degradable pigment, ultraviolet light protector, bentonite, polytetrafluoroethylene and the second aqueous solution into a high-shear stirring device, and add a dispersant, a thickener and a surfactant, then stir and mix them to obtain the outer layer material. Specifically, first add water and the dispersant into the high-shear stirring device for preliminary mixing to ensure that the dispersant can be completely dissolved in water and avoid the aggregation of solid components. Subsequently, add the degradable pigment, anti-ultraviolet agent, bentonite, polytetrafluoroethylene and the surfactant. Start with low-speed stirring and gradually increase the stirring speed to ensure that all components are evenly dispersed. The stirring time is > 30 min. Finally, add the thickener to adjust the viscosity of the coating to ensure that the coating is suitable for different coating methods such as spraying, dipping or brushing. Further, use a viscometer to test the viscosity of the coating to ensure that it meets the coating requirements. After mixing, filter the outer layer material through a 200-mesh sieve to remove large particulate matter and ensure that there will be no particulate precipitation or unevenness during the subsequent coating process.
[0043] Step Four: Treatment of the composite structure
[0044] Use the hot pressing composite method to composite the middle layer material and the inner layer material. Control the hot pressing temperature at 160 °C, the pressure at 2 MPA, and the time at 3 min to obtain a double-layer composite structure, then cool it. After that, use the coating method to coat the outer layer material onto the double-layer composite structure. Specifically, use the methods of brushing, dipping or spraying. After coating, conduct a drying treatment at 70 °C, then conduct hot pressing composite again with the same parameters as above. After composite, cool it to obtain a three-layer composite structure, thus completing the preparation of the degradable intelligent packaging material.
[0045] Therefore, the present invention adopts a three-layer composite structure:
[0046] The inner layer is used to provide degradability, antibacterial property and flexibility, and is suitable for food contact materials;
[0047] The middle layer is used to provide mechanical strength, tear resistance and enhanced strength to ensure the stability and protection of the packaging;
[0048] The outer layer is used to provide anti-ultraviolet, anti-pollution, etc., to enhance the long-term use performance of the packaging material.
[0049] Example Two
[0050] This embodiment provides a degradable intelligent packaging material. The packaging material has a three-layer composite structure, namely an outer layer, an intermediate layer, and an inner layer. The inner layer comprises raw materials in the following parts by weight: 50 parts of chitosan, 40 parts of first polylactic acid, 3 parts of tea polyphenols, 2 parts of thermochromic powder, 20 parts of pectin, and 2 parts of xylanase; the intermediate layer comprises raw materials in the following parts by weight: 20 parts of microcrystalline cellulose, 10 parts of wood fiber, 5 parts of carbon fiber, 35 parts of second polylactic acid, 30 parts of first aqueous solution, 12 parts of sodium alginate, and 15 parts of polyurethane elastomer; the outer layer comprises raw materials in the following parts by weight: 5 parts of degradable pigment, 5 parts of ultraviolet absorber, 5 parts of bentonite, 3 parts of polytetrafluoroethylene, 30 parts of second aqueous solution, 1 part of dispersant, 1 part of surfactant, and 2 parts of coupling agent. The dispersant is polyacrylate, the surfactant is polyvinyl alcohol, the thickener is carboxymethyl cellulose, the ultraviolet absorber is titanium dioxide, and the coupling agent is silane coupling agent.
[0051] The thickness ratio of the outer layer, intermediate layer, and inner layer is 4:2:4.
[0052] The particle size of the degradable pigment is ≤10 μm, the particle size of the ultraviolet absorber is ≤150 nm, and the particle size of the bentonite is ≤10 μm.
[0053] According to Figure 1 as shown, this embodiment provides a preparation method of a degradable intelligent packaging material, comprising the following steps:
[0054] Step 1. Treatment of the inner layer material
[0055] First, add chitosan in a ratio of (1:3) to a solvent (acetic acid solution) and stir to dissolve it. During this process, the temperature is maintained at 55°C. Then add tea polyphenols, thermochromic powder, and pectin, and continue to stir. During the above process, use ultrasonic dispersion for stirring, with each stirring time >50 min. Finally, add xylanase. At this time, the temperature is reduced to 25°C, and after stirring for 30 min, a first mixed solution is obtained. Then add it together with polylactic acid to a twin-screw extruder at a temperature of 220°C. After extrusion, use a blown film machine to form a film to obtain the inner layer material.
[0056] Step 2. Treatment of the intermediate layer material
[0057] Add microcellulose, wood fiber, carbon fiber, sodium alginate and the first aqueous solution into a high-shear stirring device for mixing. The mixing time is > 30 min to obtain a second mixed solution. Then add it together with polylactic acid and polyurethane elastomer into a twin-screw extruder for melt blending at a temperature of 220 °C. After extrusion, use a blown film machine to form a film to obtain the intermediate layer material. During this process, the high-shear stirring device ensures that all materials are evenly dispersed in the solution, avoiding aggregation and stratification phenomena. This is crucial for improving the mechanical properties and stability of the intermediate layer material. The twin-screw extruder can provide efficient mixing and sufficient heat transfer during the blending process, ensuring the uniformity of each component and being able to control the extrusion temperature to prevent component degradation or performance loss due to excessive temperature.
[0058] Correspondingly, by adding reinforcing materials such as microcellulose, wood fiber, and carbon fiber, the mechanical properties of the intermediate layer can be significantly improved, enhancing the tensile strength, tear resistance, and compressive resistance.
[0059] Furthermore, a dispersant can also be added during the mixing process.
[0060] Step 3. Treatment of the outer layer material
[0061] Add the degradable pigment, ultraviolet light protector, bentonite, polytetrafluoroethylene and the second aqueous solution into a high-shear stirring device, and add a dispersant, thickener and surfactant for stirring and mixing to obtain the outer layer material. Specifically, first add water and the dispersant into the high-shear stirring device for preliminary mixing to ensure that the dispersant can be completely dissolved in water and avoid aggregation of solid components. Then add the degradable pigment, anti-ultraviolet agent, bentonite, polytetrafluoroethylene and surfactant. Start with low-speed stirring and gradually increase the stirring speed to ensure that all components are evenly dispersed. The stirring time is > 30 min. Finally, add the thickener to adjust the viscosity of the coating to ensure that the coating is suitable for different coating methods such as spraying, dipping or brushing. Further, use a viscometer to test the viscosity of the coating to ensure that it meets the coating requirements. After mixing, filter the outer layer material through a 200-mesh sieve to remove large particle substances to ensure that there will be no particle precipitation or unevenness during the subsequent coating process.
[0062] Step 4. Treatment of the composite structure
[0063] Using the hot pressing and composite method, the intermediate layer material and the inner layer material are composite. The hot pressing temperature is controlled at 200 °C, the pressure is 5 MPA, and the time is 5 min to obtain a double-layer composite structure. Then, it is cooled. After that, the outer layer material is coated on the double-layer composite structure by the coating method. Specifically, it is carried out by brushing, dipping or spraying. After coating, it is dried at 70 °C, and then hot pressing and composite are carried out with the same parameters as above. After composite, it is cooled to obtain a three-layer composite structure, completing the preparation of the degradable intelligent packaging material.
[0064] Example 3
[0065] This example presents a degradable intelligent packaging material. The packaging material is a three-layer composite structure, namely the outer layer, the intermediate layer and the inner layer. The inner layer includes the following raw materials in parts by weight: 45 parts of chitosan, 35 parts of the first polylactic acid, 2 parts of tea polyphenols, 1.5 parts of thermochromic powder, 15 parts of pectin and 1.5 parts of xylanase; the intermediate layer includes the following raw materials in parts by weight: 15 parts of microcellulose, 8 parts of wood fiber, 3 parts of carbon fiber, 32 parts of the second polylactic acid, 20 parts of the first aqueous solution, 11 parts of sodium alginate and 13 parts of polyurethane elastomer; the outer layer includes the following raw materials in parts by weight: 3 parts of degradable pigment, 4 parts of ultraviolet absorber, 3 parts of bentonite, 2 parts of polytetrafluoroethylene, 21 parts of the second aqueous solution, 1 part of dispersant, 1 part of surfactant and 1 part of coupling agent. The dispersant is polyacrylate, the surfactant is polyvinyl alcohol, the thickener is carboxymethyl cellulose, the ultraviolet absorber is titanium dioxide, and the coupling agent is silane coupling agent.
[0066] The thickness ratio of the outer layer, the intermediate layer and the inner layer is 3:3:4.
[0067] The particle size of the degradable pigment is ≤10 μm, the particle size of the ultraviolet absorber is ≤150 nm, and the particle size of the bentonite is ≤10 μm.
[0068] According to Figure 1 As shown, this example provides a preparation method of a degradable intelligent packaging material, including the following steps:
[0069] Step 1. Treatment of the inner layer material
[0070] First, chitosan is added to the solvent (acetic acid solution) in a ratio of (1:4) and stirred for dissolution. During this process, the temperature is maintained at 55 °C. Then, tea polyphenols, thermochromic powder and pectin are added, and stirring continues. During the above process, ultrasonic dispersion is used for stirring, and each stirring time is >50 min. Finally, xylanase is added. At this time, the temperature is reduced to 25 °C. After stirring for 25 min, a first mixed solution is obtained. Then, it and polylactic acid are added into a twin-screw extruder at a temperature of 210 °C. After extrusion, it is formed into a film by a blown film machine to obtain the inner layer material.
[0071] Step 2. Treatment of the intermediate layer material
[0072] Add microcellulose, wood fiber, carbon fiber, sodium alginate and the first aqueous solution into a high-shear stirring device for mixing. The mixing time is > 30 min to obtain a second mixed solution. Then add it together with polylactic acid and polyurethane elastomer into a twin-screw extruder for melt blending at a temperature of 210°C. After extrusion, use a blown film machine to form a film to obtain the intermediate layer material. During this process, the high-shear stirring device ensures that all materials are evenly dispersed in the solution, avoiding aggregation and stratification phenomena. This is crucial for improving the mechanical properties and stability of the intermediate layer material. The twin-screw extruder can provide efficient mixing and sufficient heat transfer during the blending process, ensuring the uniformity of each component and being able to control the extrusion temperature to prevent component degradation or performance loss due to excessive temperature.
[0073] Correspondingly, by adding reinforcing materials such as microcellulose, wood fiber, and carbon fiber, the mechanical properties of the intermediate layer can be significantly improved, enhancing the tensile strength, tear resistance, and compressive resistance.
[0074] Furthermore, a dispersant can also be added during the mixing process.
[0075] Step 3. Treatment of the outer layer material
[0076] Add the degradable pigment, ultraviolet light protector, bentonite, polytetrafluoroethylene and the second aqueous solution into a high-shear stirring device, and add a dispersant, thickener and surfactant for stirring and mixing to obtain the outer layer material. Specifically, first add water and the dispersant into the high-shear stirring device for preliminary mixing to ensure that the dispersant can be completely dissolved in water and avoid aggregation of solid components. Then add the degradable pigment, anti-ultraviolet agent, bentonite, polytetrafluoroethylene and surfactant. Start with low-speed stirring and gradually increase the stirring speed to ensure that all components are evenly dispersed. The stirring time is > 30 min. Finally, add the thickener to adjust the viscosity of the coating to ensure that the coating is suitable for different coating methods such as spraying, dipping or brushing. Further, use a viscometer to test the viscosity of the coating to ensure that it meets the coating requirements. After mixing, filter the outer layer material through a 200-mesh sieve to remove large particulate matter to ensure that there will be no particulate precipitation or unevenness during the subsequent coating process.
[0077] Step 4. Treatment of the composite structure
[0078] Using the hot pressing composite method, the intermediate layer material and the inner layer material are compounded. The hot pressing temperature is controlled at 200 °C, the pressure is 4 MPA, and the time is 4 min to obtain a double-layer composite structure. Then, it is cooled. After that, the outer layer material is coated on the double-layer composite structure by the coating method. Specifically, it is carried out by brushing, dipping or spraying. After coating, it is dried at 70 °C, and then hot pressing composite is carried out with the same parameters as above. After composite, it is cooled to obtain a three-layer composite structure, and the preparation of the degradable intelligent packaging material is completed.
[0079] The biodegradation rates of the degradable intelligent packaging materials prepared in Example 1, Example 2 and Example 3 are measured. Standard methods such as GB / T 19277.1-2011 are used. Specifically, the experimental conditions are as follows:
[0080] The material samples are tested under controlled composting conditions. The composting temperature is maintained at about 58 °C, and the humidity and oxygen conditions are controlled within appropriate ranges to simulate the natural composting process. The samples are sampled at regular intervals to measure the mass change and analyze the degradation of the materials.
[0081] After measurement, the biodegradation rates of this material under controlled composting conditions are all ≥90%, indicating that the material can be rapidly degraded in the composting environment and converted into harmless substances such as water and carbon dioxide, meeting the environmental protection requirements.
[0082] Then, a hydrolysis environment is simulated (the material samples are immersed in water, the water temperature and water quality are controlled, and samples are taken regularly to measure the mass loss and observe the degradation of the materials in the water environment). The degradation rate reaches more than 90% within 6 to 12 months, indicating that the material has good degradation performance in the hydrolysis environment, can be decomposed in a short time, meets the biodegradability standard, and will not cause long-term pollution to the environment.
[0083] For food safety, the raw material components of the present invention are all safe and non-toxic raw materials. Therefore, the packaging material will not release toxic and harmful substances and meets the food safety requirements.
[0084] The degradable intelligent packaging materials prepared in Example 1, Example 2 and Example 3 are cut into small samples (10×10 cm), placed in a temperature-controlled experimental device (temperature control box), and different temperatures (5 °C, 20 °C, 40 °C, 60 °C, 80 °C) are set. At the same time, the color change of the packaging material is observed each time the temperature is changed, and the change situation at different temperatures is recorded. Then, a color difference meter is used to quantitatively analyze the color change of the material. Correspondingly, the color difference meter can measure the color change of the packaging material and represent the degree of color change with a numerical value (ΔE value). The larger the ΔE value, the more obvious the color change. Thus, a temperature response test is carried out as shown in Table 1 below:
[0085] Table 1
[0086] Temperature (°C) Initial Color Color Change ΔE Value 5 Transparent No Significant Change 0 20 White Minor Change 0.5 40 Light Yellow Slight Change 1.2 60 Yellow Obvious Change 3.4 80 Red Significant Change 6.8
[0087] As shown in Table 1 above, it shows that the degradable intelligent packaging material obtained by the present invention can respond to temperature changes and achieve the expected color change effect.
[0088] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments. What is described in the above embodiments and the specification only illustrates the principles of the present invention. Without departing from the framework and scope of application of the present invention, the present invention will have various changes and improvements, and these changes and improvements all fall within the scope of the present invention claimed. The scope of protection claimed by the present invention is defined by the appended claims and their equivalents.
Claims
1. A degradable intelligent packaging material, characterized in that: The packaging material is a three-layer composite structure, namely an outer layer, a middle layer and an inner layer. The inner layer comprises the following raw materials in parts by weight: 40-50 parts of chitosan, 30-40 parts of first polylactic acid, 1-3 parts of tea polyphenols, 0.5-2 parts of thermochromic powder, 10-20 parts of pectin and 0.5-2 parts of xylanase; the middle layer comprises the following raw materials in parts by weight: 10-20 parts of microcellulose, 5-10 parts of wood fiber, 1-5 parts of carbon fiber, 30-35 parts of second polylactic acid, 10-30 parts of first aqueous solution, 10-12 parts of sodium alginate and 10-15 parts of polyurethane elastomer; the outer layer comprises the following raw materials in parts by weight: 1-5 parts of degradable pigment, 3-5 parts of ultraviolet light absorber, 2-5 parts of bentonite, 1-3 parts of polytetrafluoroethylene, 10-30 parts of second aqueous solution, 0.5-1 part of dispersant, 0.5-1 part of surfactant and 0.5-2 parts of coupling agent.
2. The biodegradable intelligent packaging material according to claim 1, wherein: The thickness ratio of the outer layer, the middle layer and the inner layer is (3-4):(2-3):(3-4).
3. The degradable intelligent packaging material according to claim 1, wherein: The particle size of the degradable pigment is ≤10 μm; the particle size of the ultraviolet light absorber is ≤150 nm; the particle size of the bentonite is ≤10 μm.
4. The degradable intelligent packaging material according to claim 1, wherein: The dispersant is polyacrylate; the surfactant is polyvinyl alcohol; the thickener is carboxymethyl cellulose; the ultraviolet light absorber is titanium dioxide; the coupling agent is silane coupling agent.
5. A preparation method of a degradable intelligent packaging material, characterized in that: It includes the following steps: Step 1. Treatment of the inner layer material First, stir and dissolve chitosan with a solvent, then add tea polyphenols, thermochromic powder and pectin, continue to stir, and finally add xylanase. After stirring for 15-30 min, a first mixed solution is obtained, and then it and polylactic acid are added into a twin-screw extruder and extruded into a film to obtain the inner layer material; Step 2. Treatment of the middle layer material Add microcellulose, wood fiber, carbon fiber, sodium alginate and the first aqueous solution into a high-shear stirring device for mixing to obtain a second mixed solution, and then it, polylactic acid and polyurethane elastomer are added into a twin-screw extruder and extruded into a film to obtain the middle layer material; Step 3. Treatment of the outer layer material Add the degradable pigment, ultraviolet light protector, bentonite, polytetrafluoroethylene and the second aqueous solution into a high-shear stirring device, and add the dispersant, thickener and surfactant, and stir and mix to obtain the outer layer material; Step 4. Treatment of the composite structure Using the hot pressing and composite method, the middle layer material and the inner layer material are composite to obtain a double-layer composite structure. Then, the outer layer material is coated on the double-layer composite structure by the coating method, and then hot pressing and composite are carried out to obtain a three-layer composite structure, completing the preparation of the degradable intelligent packaging material.
6. The biodegradable intelligent packaging material according to claim 5, characterized in that: In the step 1, the solvent is acetic acid solution, and the addition ratio of it to chitosan is 3-5:
1.
7. The degradable intelligent packaging material according to claim 5, characterized in that: In the step 1, ultrasonic dispersion is adopted for stirring, and the stirring time each time is >50 min.
8. The biodegradable intelligent packaging material according to claim 5, wherein: In the step 2 and step 1, the temperature in the twin-screw extruder is 170°C-220°C.